67.5k views
6 votes
(2x^2)^3(-x^4)

can some body help please on this Algerbra my techer is not responding bsck to me

User Ktr
by
5.0k points

1 Answer

12 votes

Answer:


-8x^(10)

Explanation:


(2x^2)^3(-x^4)

Apply the rule
(-a)=-(a):


\implies -(2x^2)^3(x^4)

Apply the exponent rule
(a \cdot b)^c=a^cb^c :


\implies-(2^3\cdot x^(2 * 3))x^4


\implies -8 \cdot x^6 \cdot x^4

Apply exponent rule
a^b \cdot a^c=a^(b+c)


\implies -8x^(6+4)


\implies -8x^(10)

User Gerald Davis
by
5.9k points